Karakteristik pasien dan hubungannya dengan kepuasan terhadap pelayanan di instalasi gawat darurat - Loura Caroline Korengkeng; Ferdy Lainsamputty (STIKes Al-Insyirah Pekanbaru, 2022)
Many factors play a role in the level of satisfaction among patients in the Emergency Department (ED). Sociodemographic factors and patients’ characteristics can also potentially related to their satisfaction. This study aim was to describe patients’ satisfaction in the ED and its associated factors. A descriptive correlation and a cross-sectional approach were applied. The samples were 180 patients recruited using convenience sampling technique. Data was collected using The Short Assessment of Patient Satisfaction (SAPS) questionnaire. Descriptive statistics and bivariate analysis such as Mann-Whitney, Kruskal-Wallis, and Spearman Rank Correlation were performed to examine the relationship among variables. The type of triage had a very significant relationship with patient satisfaction in the ED (p<0,001). There was a positive and significant correlation between response time and satisfaction (r=0,164; p<0,05). Patients with lower disease severity had better satisfaction scores. The sooner the patient gets treated, the higher the satisfaction level of emergency patients.